PEMANTAPAN SUMBER PENDAPATAN DAERAH DENGAN PRIORITAS SEKTOR POTENSIAL DI KALIMANTAN - Kusumaningrum, Mayahayati (Jurnal Borneo Administrator, 2007)
“Classic” basic thought states that economics development in an area rich for natural resources will progress forward and its society is more prosperous compared with an area lack of natural resources. Kalimantan, an area rich for natural resources should realize that dependence and exploitation for a long term will harm its own territory. Therefore, to increase the regional income in the development process, Kalimantan shall increase income outside the natural resources which have enough potency to be developed that in the future it can place the oil and gas as complementary income resource. The process of this development requires association from all parties, not only local government, but also local people, along with their skill and ability as human resource in the area that will certainly support the acceleration of the development in  digging, managing and optimizing the potential sectors in the area. In the effort of searching potential sector, it is important to know the basic activities in the region as the prime mover role where every change has multiplier effects against regional economics. Through the acquisition of potential sector in the area, the attempt of policy determination in the development of an area will be more focused and efficient. Hereinafter, by having competitive advantage, development acceleration will be executed immediately.   Keywords : Sektor potensial, Pendapatan daerah